Positive end-expiratory pressure and risk of postoperative pulmonary complications in patients living at high altitudes and undergoing surgery at low altitudes: a single-centre, retrospective observational study in China - Zhuoning Li; Kaixi Shang; Zongjing Xia; Xiaoli Ye; Chongcong Gong (BMJ Open)
Objectives To examine whether a high positive end-expiratory pressure (PEEP ≥5 cmH2O) has a protective effect on the risk of postoperative pulmonary complications (PPCs) in a cohort of patients living at high altitudes and undergoing general anaesthesia.Design Retrospective, observational study.Setting A tertiary hospital in China.Participants Adult Tibetan patients living at high altitudes (≥3000 m) and who went to the low-altitude plain to undergo non-cardiothoracic surgery under general anaesthesia, from January 2018 to April 2020.Measurements This study included 1905 patients who were divided according to the application of an intraoperative PEEP: low PEEP (<5 cmH2O, including 0 cmH2O) or high PEEP (≥5 cmH2O). The primary outcome was a composite of PPCs within the first 7 postoperative days. The secondary outcomes included reintubation and unplanned intensive care unit (ICU) admission within the first 7 postoperative days and total hospital stays (day).Results The study included 1032 patients in the low PEEP group and 873 in the high PEEP group. There were no differences in the incidence of PPCs between the high and low PEEP groups (relative risk (RR) 0.913; 95% CI 0.716 to 1.165; p=0.465). After propensity score matching, 643 patients remained in each group, and the incidence of PPCs in the low PEEP group (18.0%) was higher than in the high PEEP group (13.7%; RR 0.720; 95% CI 0.533 to 0.974; p=0.033). There were no differences in the incidence of reintubation, unplanned ICU admission or hospital stays. The risk factors of PPCs derived from multiple regression showed that the application of >5 cmH2O PEEP during intraoperative mechanical ventilation was associated with a significantly lower risk of PPCs in patients from a high altitude (OR=0.725, 95% CI 0.530 to 0.992; p=0.044).Conclusions The application of PEEP ≥5 cmH2O during intraoperative mechanical ventilation in patients living at high altitudes and undergoing surgery at low altitudes may be associated with a lower risk of PPCs. Prospective longitudinal studies are needed to further investigate perioperative lung protection ventilation strategies for patients from high altitudes.Trial registration number Chinese Clinical Trial Registry (ChiCTR2100044260).